1995
DOI: 10.1007/bf00011468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water and nutrient applications in a Scots pine stand to tree growth and nutrient cycling

Abstract: In a Scots pine forest stand, demineralized water and a complete set of nutrients with water were applied to the soil by means of frequent irrigation for four years in order to eliminate water and nutrient shortage of the trees. Apart from this optimization, dissolved (NH4)2SO4 was irrigated at a rate of 120 kg N ha-1 y-l to create a situation of N excess. Effect of treatments on tree growth and chemical composition of soil water and vegetation were monitored. From the first treatment year onwards basal area g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Several studies have reported that soil acidification is caused by high load by NH 4 + -N, but not by NO 3 --N ( Rollwagen and Zasoski 1988;Wilson and Skeffington 1994a;De Visser and Van Breemen 1995). Several studies have reported that soil acidification is caused by high load by NH 4 + -N, but not by NO 3 --N ( Rollwagen and Zasoski 1988;Wilson and Skeffington 1994a;De Visser and Van Breemen 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that soil acidification is caused by high load by NH 4 + -N, but not by NO 3 --N ( Rollwagen and Zasoski 1988;Wilson and Skeffington 1994a;De Visser and Van Breemen 1995). Several studies have reported that soil acidification is caused by high load by NH 4 + -N, but not by NO 3 --N ( Rollwagen and Zasoski 1988;Wilson and Skeffington 1994a;De Visser and Van Breemen 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The few field studies on this topic mostly simulated reduced rainfall (Hanson et al, 2003;Davidson et al, 2004;Yahdjian et al, 2006;Sotta et al, 2007) or single, extreme drought periods followed either by natural wetting or artificial wetting (Borken et al, 1999(Borken et al, , 2006Emmett et al, 2004). Other approaches are the experimental increase in precipitation that allows the evaluation of natural drought events (Bloem et al, 1992;Matson et al, 1992;De Visser & van Breemen, 1995;Hanson et al, 2003) or the analysis of field observations (e.g. Jarvis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…increased the nitrate concentration in soil water. For instance, at Harderwijk the mean flux-weighted nitrate concentration increased from 173 mmolc m -3 in the control plot to 398 mmolc m -3 in the irrigated plot [De Visser and Van Breemen, 1995]. This increase can only be explained by an increase in net mineralization, especially because the dilution effect by the increased water availability would have decreased the concentration.…”
Section: At Both Dutch Sites the Increased Water Availabilitymentioning
confidence: 97%